From a dictionary to an atlas: segmental mapping of the linguistic picture of the world - S. N. Gagarin (Vestnik MGIMO-Universiteta)
'At the heart of any language lies a vision. It embraces the world around us in myriads of complex ways. It is the lifeblood of every people's identity. It is so essential and indispensable that few assets of humankind can rival it for value or timelessness. It is known as the linguistic picture of the world, and it is notorious for being among the knottiest study subjects of language science. No coherent methodology has been proposed to date as to how it should be consistently structured to result in a systemic and navigable map of its core words and concepts. This constitutes a conspicuous gap in contemporary linguistics, which the present article addresses from the perspective of cognitive lexicology and lexicography while engaging the linguistic picture of the world on a segment-by-segment basis. In keeping with the aforesaid approach, one segment at a time is selected, and the discourse that reflects it is analysed with a view to identifying transcendental notions contained therein. The latter are construed as a type of cognitive concepts which epitomise the core ideas inherent in a particular type of spoken or written discourse. Being verbalised by means of relevant verbal fields, these transcendental notions permeate the cognitive and textual fabric of the selected segment of a linguistic picture of the world. By way of demonstrating the feasibility of this approach, a new type of dictionary has been compiled by the author, which captures and reveals in a semantically structured way the verbal side of the transcendental notion "countering" in the socio-political discourse of English-language media. Along with other transcendental notions, such as "facilitation", "communication", "attitude", etc., it is viewed as part of a range of the cognitive pillars which are essential to a limited segment of a linguistic picture of the world, but are by no means reserved to it, stretching far beyond and reaching throughout the vision of the world enshrined in the English language. The present article asserts and demonstrates by example that by creating the described type of dictionaries a basis can be laid for engaging the broader linguistic picture of the world in a whole new way, as their structure enables the drawing of clear semantic boundaries between and within the verbal fields of major concepts. These, in turn, can be used for creating maps, or rather atlases, initially of the smaller segments of linguistic pictures of the world, which may over time, and with enough methodological evolution, transform into larger-scale projects covering different languages, which arguably contains a hitherto unexplored potential for comparing them at a new systemic level, that of the structure and internal semantic delimitation of linguistic pictures of the world.